Effect of Outrunning the Aquifer in Heterogeneous Water Drive Gas Reservoirs - EL-Seginy, Mahmoud Ahmed Abd EL-Hamid (AUC Knowledge Fountain, 2026)
Water-drive gas reservoirs (WDGRs) often face early water breakthrough, which can severely limit recovery efficiency—an issue particularly pronounced in heterogeneous or stratified settings. Producing gas at relatively high rates, a strategy known as “outrunning the aquifer,” has been proposed to delay water encroachment and enhance recovery factors (RF). Yet, the combined effects of aquifer size, reservoir heterogeneity, structural dip, fluid type, stratification, and vertical connectivity on the effectiveness of this strategy have not been systematically explored. Gas condensate systems were deliberately excluded from this study due to the complications of condensate banking, condensate dropout inside the reservoir, and their lack of RF improvement under increased production rates. To address this knowledge gap, nearly 1,000 reservoir simulation runs were performed. These runs systematically varied aquifer volumes, heterogeneity levels quantified by Lorenz Coefficients (LC), reservoir dip angles, gas types (dry and wet), and vertical permeability ratios. The results demonstrate that outrunning can enhance recovery by up to 15% in moderately heterogeneous systems (LC ≈ 0.3), revealing that specific idealized stratification patterns may, under certain conditions, outperform homogeneous configurations. Aquifer size proved to be a critical factor: intermediate aquifer volumes consistently yielded the largest RF improvements, whereas extremely large aquifers reduced the effectiveness of outrunning due to water compressibility counteracting additional gas recovery. Stratification effects were nuanced—low aquifer sizes in stratified reservoirs resulted in RF reductions of down to -6.45%, but this negative impact diminished as aquifer size increased. Reservoir dip also played a decisive role, with low-dip reservoirs achieving the greatest improvements, followed by moderate- and high-dip cases. Vertical permeability sensitivity showed no consistent trends, highlighting the need for further studies using dual-porosity and dual-permeability modeling. Differences between dry and wet gas were minimal, confirming that outrunning remains effective in the absence of phase change. Overall, this thesis provides a comprehensive, quantitative evaluation of the geological and physical controls governing outrunning strategies in WDGRs. The findings offer practical guidance for optimizing production strategies in reservoirs with varying aquifer support, heterogeneity, stratification, and structural geometry.